Racial differences in percentage of Hysterectomy for Common Uterine Conditions among the Hospitalized Women in the US (Journal of Surgical Sciences, 2020)
Background: Hysterectomy is the second most frequently performed operation in the United States, after cesarean section. Approximately 588,000 hysterectomies are performed annually.Objectives: To find out the racial differences in percentage of Hysterectomy for Common Uterine Conditions among the Hospitalized Women in the US.Methods: The 2001 National Inpatient Sample data was used to estimate the racial differences in the rate of the five most common uterine conditions among the hospitalized women; the same data was also used to estimate the racial differences in the percentage of those who received a hysterectomy. All hospitalized women who had a diagnosis of uterine fibroids, endometriosis, abnormal genital bleeding, genital prolapse and genital malignancy were included. The difference between rate and the percentage was calculated using Z test.Results: Of the five, the most common diagnosis, for all hospitalized women regardless of race, was uterine fibroids. But the rate of uterine fibroid diagnosis for hospitalized blacks was nearly two and onehalf times the rate for hospitalized whites (p